2019
DOI: 10.3233/bmr-181127
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative injection therapy and repetitive transcranial magnetic stimulation in primary fibromyalgia treatment: A comparative study

Abstract: RIT had the advantage in clinical and functional improvement in fibromyalgia patients, while rTMS had better results regarding depression and the cortical component of AEPs. These results might draw attention to the evaluability of a combination of both techniques for a better therapeutic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The treatment in these two RCTs consisted of 10-15 sessions of 10-Hz rTMS that targeted the left DLPFC. In 2019, Abd Elghany et al (62) prospectively recruited 120 patients with FM and compared the effectiveness of 10-Hz rTMS over the left DLPFC with prolotherapy. The results showed that the VAS scores and tenderness points were decreased in patients who received prolotherapy (60 patients) as compared with those in patients who received rTMS (60 patients); however, rTMS had better results on depression.…”
Section: Fibromyalgiamentioning
confidence: 99%
“…The treatment in these two RCTs consisted of 10-15 sessions of 10-Hz rTMS that targeted the left DLPFC. In 2019, Abd Elghany et al (62) prospectively recruited 120 patients with FM and compared the effectiveness of 10-Hz rTMS over the left DLPFC with prolotherapy. The results showed that the VAS scores and tenderness points were decreased in patients who received prolotherapy (60 patients) as compared with those in patients who received rTMS (60 patients); however, rTMS had better results on depression.…”
Section: Fibromyalgiamentioning
confidence: 99%
“…One study examined the use of rTMS in patients with fibromyalgia but lacked a sham control group, instead comparing it to prolotherapy [ 76 ]. Although recent meta-analyses have included numerous randomized controlled trials (RCTs), they have not incorporated the high-quality RCT conducted by Argaman in 2021 [ 43 ], which specifically targeted the right M1 brain region for the first time, and as described in the literature, Argaman’s study revealed significant outcomes, showing marked reductions in MPQ-VAS and BPI-severity scores, as well as decreases in FIQ and MPQ-affective scores following 10 Hz rTMS.…”
Section: Non-invasive Repetitive Transcranial Magnetic Stimulation Of...mentioning
confidence: 99%